Enhancing spectral response towards high-performance dye-sensitised solar cells by multiple dye approach: A comprehensive review - Akhtaruzzaman M.; Shahiduzzaman M.; Selvanathan V.; Sopian K.; Hossain M.I.; Amin N.; Hasan A.K.M. (Elsevier Ltd, 2023)
Absorption spectroscopy; Cell engineering; Dye-sensitized solar cells; Efficiency; Manufacture; Porphyrins; Ruthenium compounds; Water absorption; Co-sensitization; Dye- sensitized solar cells; Metal-organic co-sensitization; Metalorganics; Organic-organic co-sensitization; Organics; Panchromaticity engineering; Organometallics